اختبار ظاهرة العلة الهولندية في الجزائر - خشخوش, هاجر (University of eloued جامعة الوادي, 2017)
The Dutch disease is one of the issues which has been raised about the Algerian economy since Algeria is considered as one of the rich countries with its natural resources (oil). Algeria’s dependence on fuel exports entirely and delay of the industrial sector is one of the most important elements of such issues. This study is an attempt to test the phenomenon of Dutch disease in Algeria, where they adopted a set of economic indicators of the real effective exchange rate, the total exports and total imports of goods and services, per capita GDP, the added value of the industry, the rate of inflation. We has used the program of Eviews 9 and Micrifit 4.1 to study the stability and test the co-integration. It showed that the results of the co- integration test of a long-term relationship between all the variables of this study. The results shows the estimation of the model using the ARDL methodology that most of the variables cause the real exchange rate to rise, which is an evidence of the effects of Dutch disease in the national economy.
مذكرة ماستر تجارة دولية
Keywords: العلة الهولندية،سعر الصرف الفعلينسعر النفط،الاقتصاد الجزائري; Dutch disease, the exchange rate real, the price of oil, the Algerian economy, co- integration.